Heuristic Bias In Investment Decision Making - Latifah Wulandari Binti Asbaruna (Trigin Publisher, 2023)
The field of Behavioral Finance offers an explanation for the illogical financial decisions made by investors. This demonstrates how investors' decisions about investments are influenced by their feelings and cognitive errors. Heuristic bias is one of the many factors that contribute to behavioral finance. Essentially, the behavioral finance approach looks into the patterns of behavior exhibited by investors and attempts to determine how these patterns influence the decisions made about investments. Behavioral finance furnishes an array of valuable perspectives for investment experts, thereby furnishing investors with a structure to assess investment approaches. Analyzing how heuristic bias affects investment choices is the goal of the study. Students, who make up the target population for this study, comprise the population. According to the findings, heuristic bias significantly influences investors' decisions to make investments.